Current trends in the pragmatics of Spanish - Márquez-Reiter, Rosina; Placencia, María E. (María Elena) (Pragmatics & beyond, 2004)
Current Trends in the Pragmatics of Spanish provides the reader with a representative spectrum of current research in the most dynamic areas of the pragmatics of Spanish. It brings together a collection of academic essays written by well-established as well as emerging voices in Hispanic pragmatics. The essays include applications of pragmatic concepts to sub-fields of (Spanish) linguistics (i.e., pragmatics and grammar; pragmatics and applied linguistics; pragmatics and cross- and inter-cultural communication), studies of 'traditional' topics in pragmatics (i.e., discourse markers, politeness.